2022
DOI: 10.1111/his.14784
|View full text |Cite
|
Sign up to set email alerts
|

Update on triple‐negative breast cancers – highlighting subtyping update and treatment implication

Abstract: Triple‐negative breast cancer (TNBC) remains a major challenge in breast cancer management. Continuing research in the past years aimed at understanding the biology of this tumour and developing more effective therapeutic options. It is now clear that TNBC is vastly heterogeneous with diverse histological, molecular, immunological profiles and clinical differences. Current evidence suggested the existence of at least four predominant subtypes based on expression profiling across studies. These subtypes exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 134 publications
(304 reference statements)
1
12
0
Order By: Relevance
“…4E). The latter analysis revealed that most markers appeared correlated with regard to cell count levels, de ning at one end an immune cold subset of TNBC tumours and at the other end an immune hot tumour subset, as reported previously (10,12). Consistent with the established prognostic role of immune response in TNBC and the general immune marker-to-marker co-expression in TMA cores, patient strati cation based on automated cell counts subdivided patients in our cohort with adjuvant systemic therapy into groups with differing prognosis in terms of IDFS (Fig.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…4E). The latter analysis revealed that most markers appeared correlated with regard to cell count levels, de ning at one end an immune cold subset of TNBC tumours and at the other end an immune hot tumour subset, as reported previously (10,12). Consistent with the established prognostic role of immune response in TNBC and the general immune marker-to-marker co-expression in TMA cores, patient strati cation based on automated cell counts subdivided patients in our cohort with adjuvant systemic therapy into groups with differing prognosis in terms of IDFS (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…Still, within TNBC there is a large heterogeneity in the level of immune response observed across individual tumours (10,11). This immune heterogeneity has also been recognized in proposed transcriptional TNBC subtypes though an immunomodulatory (IM) subtype/phenotype (12). For instance, in 2011 Lehmann et al proposed the IM subtype as one of six intrinsic TNBC subtypes, but later re ned this subtyping scheme to comprise four subtypes (BL1, BL2, M, LAR) where the IM subtype can be superimposed on the former as an independent feature of the tumour (13).…”
Section: Introductionmentioning
confidence: 96%
“…Further subtyping of TNBC may aid subtype‐specific therapeutic strategies. Professor Gary Tse and colleagues 7 share an update on TNBC with highlights on subtyping and treatment (target) implications. Breast tumours with myoepithelial phenotype typically show triple negativity but they exhibit better prognosis and clinical behaviour than other TNBC.…”
Section: Updates On Diagnostic Entitiesmentioning
confidence: 99%
“…Analysis of the gene expression pattern of BC datasets discovered TNBC cellular heterogeneity grouped under six molecular subtypes: basal-like (BL1 & BL2), mesenchymal, mesenchymal stem-like, luminal androgen receptor subtype, and immunomodulatory [ 32 ]. Chemotherapy remains the standard treatment for patients even if TNBC is divided into six types of tumors.…”
Section: Introductionmentioning
confidence: 99%